Making the Abnormal Normal: Maximizing Diversity in a Virtual Environment - Mary T Dzindolet; Stephanie Boss; Krystal Brue; Shaun Calix; Jennifer Dennis (Academic Chairpersons Conference Proceedings, 2022)
With the polarization of opinions around COVID 19, chairs and deans must become experts at navigating conflict and creating synergy from diversity, oftentimes while communicating virtually. Four chairs (of Business, Education and Sports & Exercise Science, Social Sciences, and Psychology Departments), and their dean, will share strategies for encouraging the expression of diverse opinions in virtual faculty meetings.
Keywords: teamwork; conflict resolution; diversity; synergy; virtual meetings